Integrity of RNA in long-term-stored cervical liquid-based cytology samples: implications for biomarker research - Madeleine P J White; Andrew Stevenson; Hana Elasifer; Chris Davis; Kyriaki Nomikou; Kate Cuschieri; Sheila V Graham (BioTechniques)
Biobanks of cervical screening (LBC) samples annotated with disease status are an invaluable resource to support the development of tools for the risk stratification of disease. Although there is growing interest in the assessment of RNA-based biomarkers, little is known on the suitability and durability of stored clinical samples (commonly used in cervical screening) to support RNA-based research. RNA was extracted from 260 stored LBC samples. Storage at -80°C or -25°C allowed isolation of sufficient RNA for further analysis. RNA was found to be substantially degraded according to Agilent Bioanalyser data. Despite this, RT-qPCR was successful in 95% samples tested. These data suggest that biobanked LBC samples are suitable for RNA-based assessment even if stored for up to 14 years.